"Strict injunctions that the dogs should not be risked": A revised hypothesis for this anecdote and others in narratives of Scott's last expedition. (26th November 2019) - May, Karen; Lewis, George
Abstract: This article updates Karen May's earlier 2012 hypothesis ( Could Captain Scott have been saved? Revisiting Scott's last expedition ). In this revised hypothesis, Cecil Meares, not Surgeon E. L. Atkinson, originated the unsubstantiated statement that "Strict injunctions had been given by Scott that the dogs should not be risked in any way." This hypothesis incorporates new information uncovered since 2012, specifically Meares' misrepresentations during the Terra Nova expedition; Atkinson's 1911 journal entries; Atkinson's 1919 allegation that Meares had "disobeyed orders"; and Tryggve Gran's "The Race for the South Pole between Scott and Amundsen", a 1945/post-1945 document that appears to have been Roland Huntford's source for anecdotes in Huntford's 1979 Scott–Amundsen biography. The article gives a proposed chronology for how Meares' early misrepresentations and Gran's later misunderstandings influenced the decisions, and later presentations, of the Terra Nova expedition.